A Short Research in Danish Cardinal and Ordinal Numerals on Indo-European Background - Garczyński, Błażej (Folia Scandinavica Posnaniensia, 2014)
The article focuses on the Danish numerals 1-1000. It presents their Proto-Indo-European, Proto-Germanic, Old Danish and present forms whilst providing additional information on their development and corresponding numerals in other European languages. It focuses primarily on the vigesimal counting system, whose traces can be found in Danish, and which is the source of some unique forms unseen in other languages. Therefore, special attention is paid to the numerals of the series 50-90. Though these appear to be unique and exotic, the article shows that they are not to be perceived as an anomaly but rather a different path of development within the language Moreover, a brief explanation of the origins of the vigesimal system in Danish is provided. Also, several units of measurement showing traces of the vigesimal, duodecimal and sexagesimal systems are discussed. Finally, language reforms aimed at changing the numeral forms will be shortly portrayed.